Edukasi Pengelolaan Lingkungan Proklim Dalam Budidaya Tanaman Organik Potensial Di Kelurahan Sidomulyo Timur - Yustina, Yustina; Taufik, Hendra; Wirayudha Sinaga, Raja; Mas Arya, Andi; Aourah, Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Climate change has a major impact on human health, food security, and economic development, so it is necessary to improve the ability to adapt to the impacts of climate change and a series of activities to reduce greenhouse gas emissions as a form of mitigation of the impacts of climate change. The climate change control effort launched by the government is to encourage multi-stakeholder cooperation to strengthen climate change adaptation and mitigation capacity at the community-based site level through the implementation of the Climate Village Program (ProKlim). This writing aims to determine the application of environmental management education in potential organic plant cultivation activities in East Sidomulyo Village Especially Integrated Women Group (KWT) in Sidomulyo Timur. The method used in this service is a participatory method, which involves the community as a subject in development. The provision of seed houses to help the community and integrated women's groups in East Sidomulyo Village in organic plant cultivation activities provides many benefits from various economic, health, socio-cultural aspects of the community, and environmental sustainability.